Free radicals and the pancreatic acinar cells: role in physiology and pathology - Chvanov, M (The Royal Society, 2005)
Reactive oxygen and nitrogen species (ROS and RNS) play an important role in signal transduction and cell injury processes. Nitric oxide synthase (NOS)—the key enzyme producing nitric oxide (NO)—is found in neuronal structures, vascular endothelium and, possibly, in acinar and ductal epithelial cells in the pancreas. NO is known to regulate cell homeostasis, and its effects on the acinar cells are reviewed here. ROS are implicated in the early events within the acinar cells, leading to the development of acute pancreatitis. The available data on ROS/RNS involvement in the apoptotic and necrotic death of pancreatic acinar cells will be discussed.